Oral health and emotional well-being in premenopausal and postmenopausal women: a cross-sectional cohort study - Nil Yakar; Asena Türedi; Gülnur Emingil; Çağdaş Şahin; Timur Köse; Angelika Silbereisen; Nagihan Bostanci (BMC, 2021)
Abstract Background Menopause, the absence of ovarian sex steroids, is frequently accompanied by emotional and physiological changes in a woman´s body, as well as oral health changes. The present study aimed to evaluate the association between the periodontal health status and emotional and physical well-being among postmenopausal women (PMW) in comparison with regularly menstruating premenopausal women (RMPW). Methods A total of 115 women (PMW, n = 56, mean age ± SD: 54 ± 5; RMPW, n = 59, mean age ± SD: 41 ± 4) received a comprehensive medical assessment and a full-mouth oral examination. All completed the Women's Health Questionnaire (WHQ) to measure emotional and physical well-being. The corresponding bone mineral density (BMD) scores were obtained from participants´ medical records. Results Tooth loss was significantly higher in PMW than RMPW after adjusting for age (3.88 ± 2.41 vs 2.14 ± 2.43, p < 0.05). No significant difference was found in the prevalence of periodontitis between the two groups (PMW: 39.2%, RMPW: 32.2%, p > 0.05). The prevalence of periodontitis was associated with fewer daily brushing sessions in PMW (p = 0.021). Based on the WHQ, both PMW and RMPW with periodontitis had higher ''depressed mood'' scores compared to periodontally healthy women (p = 0.06 and p = 0.038, respectively). The women who reported fewer daily toothbrushing sessions found to have higher depressive mood scores (p = 0.043). Conclusions Presence of periodontitis is associated with the emotional and physical well-being of women and reinforcement of oral healtcare is recommended at different stages of a woman's life including menopause to reduce the risk for early tooth loss in women.